Understanding and using english grammar - Azar, Betty Schrampfer (Thanh niên, 2000)
A classic developmental skills text for intermediate to advanced students of English, Understanding and Using English Grammar is a comprehensive reference grammar as well as a stimulating and teachable classroom text.